Longitudinal Assessment of Antimicrobial Susceptibility among Gram-Negative and Gram-Positive Organisms Collected from Italy as Part of the Tigecycline Evaluation and Surveillance Trial between 2004 and 2011 - Michael J. Dowzicky; Stefania Stefani (MDPI AG, 2013)
The Tigecycline Evaluation and Surveillance Trial (T.E.S.T.) was initiated in 2004 to longitudinally monitor the activity of the broad-spectrum glycylcycline antimicrobial tigecycline, and a suite of comparator agents, against an array of clinically important bacterial pathogens worldwide. In this report, we examine the activity of tigecycline and comparators against a collection of 13,245 clinical isolates, both Gram-positive (n = 4,078 and Gram-negative (n = 9,167), collected from 27 centres in Italy between 2004 and 2011. Susceptibility was established according to Clinical Laboratory Standards Institute guidelines. Tigecycline and linezolid exhibited very good activity against Gram-positive pathogens, with MIC90s ranging from 0.06 to 0.25 mg/L and 1-4 mg/L, respectively; vancomycin and the carbapenems also showed good activity against select Gram-positive pathogens. Tigecycline was the most active agent against Gram-negative pathogens (except P. aeruginosa), with MIC90s ranging from 0.25-2 mg/L (16 mg/L for P. aeruginosa). Amikacin and the carbapenems also possessed good activity against many Gram-negative pathogens here. ESBL-positive E. coli increased in prevalence from 2004 to 2011, while ESBL-positive Klebsiella spp., vancomycin-resistant enterococci and MRSA decreased in prevalence. Linezolid, tigecycline and vancomycin susceptibility were very stable over the course of this study, while susceptibility to ampicillin, piperacillin-tazobactam, ceftriaxone and levofloxacin varied over time according to pathogen; minocycline and cefepime susceptibility among several pathogens decreased during this study.